A interdiscursividade na autoajuda: imbricações e desdobramentos na compreensão do ethos leitor - Santos, Claudiana dos (2024)
This thesis is based on the fields of rhetorical, discursive and argumentative studies. The starting point of this investigation is the following problem: amid the epistemological relevance of the reading theme, how to understand the discursive images of reading and the ethos of readers invested with values historically associated with the (inter)discursivities of self-help books? In this sense, the general objective of the study is to analyze how interdiscursivity, in self-help, acts as a discursive strategy and what are the developments in the ethos of the reader of books of this genre. For the analytical device, categories provided by New Rhetoric and Discourse Analysis were selected. Furthermore, emphasis was placed on the constructs of Perelman and Olbrechts-Tyteca (2005), Amossy (2016, 2020, 2022), Maingueneau (2008a, 2008b, 2011, 2016, 2018), Galinari (2009), Meyer (1993, 2007) and Paveau (2017). For the analysis of reading practices, the method sought support from Alves and Rojo (2020), Orlandi (2003, 2008),Curcino (2020) and Rouxel (2012). The research is characterized by a qualitative approach. The methodological archetype consists of three stages. Initially, book titles with the highest sales rates between 2010 and 2022 were cataloged. Next, an analytical model for evaluation readers was created, based on the categorization of digital comments (Paveau, 2017). In the third stage, reading experiences were collected through an online questionnaire. In these circumstances, the analyzes of two books were investigated: Mais esperto que o diabo (Hill, 2014) and Nunca desista dos seus sonhos (Cury, 2007). With the support of WebQDA software, data sources were triangulated (books, comments and questionnaires).The results obtained showed how self-help books are supported in the discursive fields that allude to the following spaces: religious, pedagogical, medicinal (health), capitalist (neoliberal), psychological and advertising, therefore, support is found to assert that interdiscursivity is a founding discursive strategy of the multisemic architecture of self-help discourse and this strategy has repercussions on the unfolding of a dichotomous reading ethos (proud/shameful). After triangulating the data, it was verified how topics linked to pathos (pathemic processes) were crucial for understanding the proud/ shameful/ floating reader ethos, identified from spaces and points that lead to moral edification and multiple improvements. This research mobilized analyzes that attest to the dialogical relevance between disciplines such as Discourse Analysis and rhetorical- argumentative studies, in addition, it was possible to contribute to reader enunciability and the problematization of stereotypes, such as that the "good reader" is that of works related to "high literature" . Though the values found in the discourses analyzed, we understand that there is the presentation of a double identity resulting from the difference relative to the other and a group identity. Observing the experiential dimension in Maingueneau (2018), it is understood that the paradoxical ethos of self-help generates a confrontation between the image engendered for this reader in the works and the image produced by the real reader, thus, it is considered that the reader ethos goes through a semic intercurrence (unexpected meaning effects) due to interdiscursive strategies.